Design and Implementation of LPG Leakage Detection System using IoT-based Regulator Lever Automation on a Household Scale - Lusiana Sinaga; Suratun Nafisah; Khansa Salsabila Suhaimi; Muhammad Akmal Shani (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2024)
Liquefied Petroleum (LPG) is very common in daily cooking activities. Therefore, preventive measures must be taken to reduce the risk of fire and explosion due to LPG leakages. One action that can be taken is to install a regulator lever that can open automatically when a leakage is detected. In this research, Pulse Width Modulation (PWM) is used to control the rotational speed of the servo motor on the regulator lever, which aims to implement an automatic control system that is responsive when an LPG leakage is detected. Using servo motor control to automatically open the regulator lever can reduce the impact of accidents or losses due to LPG leakages. The test results show that the regulator lever can be opened effectively with a pulse value of 0.55 ms at a rotation angle of 0° in 0 seconds, while it can be closed with a pulse value of 2.45 ms at an angle rotation of 180° in 1.66 seconds. This shows that the regulator responds appropriately to the level of danger detected and is precise in adjusting position. The use of PWM on servo motors in the regulator control system has proven effective in increasing responsiveness to LPG leakages, as seen from the fast response (0 to 1.66 seconds) and accuracy (100% success percentage for 15 trials). This shows that using PWM can respond to emergencies quickly and precisely.